Spontaneously quenched γ-ray spectra from compact sources - Petropoulou, M.; Arfani, D.; Mastichiadis, A. (2013)
Aims: We have studied a mechanism for producing intrinsic broken power-law γ-ray spectra in compact sources. This is based on the principles of automatic photon quenching, according to which γ-rays are being absorbed on spontaneously produced soft photons whenever the injected luminosity in γ-rays lies above a certain critical value. Methods: We derived an analytical expression for the critical γ-ray compactness in the case of power-law injection. For the case where automatic photon quenching is relevant, we calculated analytically the emergent steady-state γ-ray spectra. We also performed numerical calculations in order to back up our analytical results. Results: We show that a spontaneously quenched power-law γ-ray spectrum obtains a photon index 3Γ/2, where Γ is the photon index of the power-law at injection. Thus, large spectral breaks of the γ-ray photon spectrum, e.g. ΔΓ ≳ 1, can be obtained by this mechanism. We also discuss additional features of this mechanism that can be tested observationally. Finally, we fit the multiwavelength spectrum of a newly discovered blazar (PKS 0447-439) by using such parameters to explain the break in the γ-ray spectrum by means of spontaneous photon quenching, under the assumption that its redshift lies in the range 0.1 < z < 0.24.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; BL Lacertae objects: general; gamma rays: general; radiation mechanisms: non-thermal